Bioinvasão: Impacto potencial de espécies invasoras na zona costeira marinha - Souza, Avila Pricila Silva Lins (2018)
Invasive alien species are those that are outside their natural range and that thrive in their new environment, causing ecological and economic impacts. Invasive species can impact on the abundance, richness, and composition of native community species, as well as altering ecosystem properties or processes. These species can also cause major economic losses, such as cultivation losses, fishing, silviculture and grazing capacity. In Brazil, some surveys have been carried out for the registration of exotic marine species, but the Brazilian legislation related to the prevention and control of these species still has difficulties for its implementation. One of the introductions with great expansion and abundance along the Brazilian coast is the bivalve Isognomon bicolor. In addition to the ecological damage that I. bicolor may be causing to native species, the invasive bivalve has caused economic damages to the marine activities due to biofouling in ships and port constructions. This work evaluated the impact of the invasive bivalve I. bicolor in the native benthic community, through an in situ experiment, where the invasive species was removed and the monthly monitoring of the native community was carried out in the course of one year. The analyzes revealed significant changes in the structure of the native benthic community, in terms of composition, abundance, richness and diversity of species, as a consequence of the introduction of the bioinvasor I.bicolor. Knowledge about all interactions between biotic invaders and native species is of extreme importance in assessing the impacts these species may have on ecosystems and can provide subsidies to improve environmental degradation and prevent future invasions